Factors affecting the implementation of e-teaching in Iraqi higher education - Kadum Ali Ahmed, 1970- , author 601754; Rosmah Ali, supervisor; Sekolah Informatiks Termaju 506658 (Kuala Lumpur : Universiti Teknologi Malaysia, 2014)
Thesis